Penggunaan Pupuk Kompos Untuk Hasil Benih Kacang Panjang (Vigna sinensis L.) di Subak Basang Be - NI PUTU SUCITA ANGGRAENI; I GUSTI NGURAH RAKA; I KETUT ARSA WIJAYA (Fakultas Pertanian Universitas Udayana, 2017)
Use Of Manure Composting For Seed Of Long Beans (Vigna sinensis L.) in Subak Basang Be. This study was conducted in March 2015 until July 2015 in Subak Basang Be, Village Perean, Baturiti District, Tabanan, Bali, aims to test the use of a dose of fertilizer which can provide the seed with the highest quantity and determine the effect of compost on the quality physical and physiological seed beans. This study uses a randomized block design (RAK) with 5 treatments and 5 replications. The fifth is the control treatment (P0), 5 t/ha (P1), 10 t/ha (P2), 15 t/ha (P3), and 20 t/ha (P4). The results showed that a dose of compost 10 t/ha enhances growth and yield. Seed yield per hectare obtained as much as 381.43 kg/ha, the seed is the same height as that obtained at a dose of 15 t/ha and 20 t/ha. The treatment dosages of 10 t/ha can improve physiological seed quality (germination (96.80%) and vigor storability (68.40%)). Value germination and vigor power savings as high as those achieved at a dose of 15 t/ha and 20 t/ha.